Study of influence of the demographic components in long-term unemployment - Κωστάκη Αναστασία; Ιωακείμογλου Ηλίας (The Greek Review of Social Research, 1997)
Analysis of Labour Force Survey data (1994) provides evidence there is growing concentration of unemployment in the group of persons being unemployed for two years or more. The probability of being unemployed for more than 24 months depends on age, gender and marital status. Some insight of the relative importance of personal characteristics is obtained through statistical analysis (Logistic regression). Women aged 30-44 have the maximum probability of being unemployed for more than 24 months. On the contrary, men -especially younger men- have the minimum probability.